2018
DOI: 10.1590/0366-69132018643702312
|View full text |Cite
|
Sign up to set email alerts
|

Influência da cristalização na dureza, módulo de elasticidade e tenacidade à fratura por indentação em vitrocerâmicas de dissilicato de lítio (Li2 O.2SiO2 )

Abstract: INTRODUÇÃOOs vidros são considerados materiais frágeis e os defeitos existentes na superfície são precursores de trincas, resultando em baixa resistência mecânica. Os defeitos podem surgir devido à exposição dos vidros à umidade atmosférica ou a danos mecânicos [1]. Assim, os tratamentos térmicos que promovem a cristalização constituemse em eficientes métodos para aumentar a resistência mecânica desses materiais frágeis. O tratamento térmico ResumoO efeito da cristalização sobre as propriedades mecânicas (dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was observed that ceramics with the highest percentage of crystalline phase presented secondary radial cracks and lateral cracks in a greater quantity. When analyzing the glass-ceramics with a low crystalline fraction, few secondary radial cracks were observed; however, they were larger and more defined primary cracks [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that ceramics with the highest percentage of crystalline phase presented secondary radial cracks and lateral cracks in a greater quantity. When analyzing the glass-ceramics with a low crystalline fraction, few secondary radial cracks were observed; however, they were larger and more defined primary cracks [ 24 ].…”
Section: Discussionmentioning
confidence: 99%